Water Turbidity Detection Device Using Turbidity Sensor Based On Arduino Uno - Linda Noviasari; Asni Tafrikhatin; Juri Benedi; Vicky Oby Syahputra (Jurnal E-Komtek, 2024)
A water turbidity detector using an Arduino Uno based turbidity sensor is a solution to measure water turbidity. The turbidity sensor functions to measure the level of water turbidity by detecting dissolved solid particles in it. The use of Arduino Uno as the main microcontroller, turbidity sensor to measure the level of turbidity and the results can be displayed clearly on the LCD. The main advantage of this tool is its ability to provide information about water turbidity. The integrated LED and Buzzer also provide notification if the water turbidity level has been set. In addition, the simplicity of use and integration between the turbidity sensor, Arduino Uno, LED, LCD, and buzzer on one microcontroller board provides convenience for users. The outputs of this system are LCD, LED and buzzer, and the entire input-output system is integrated by one arduino uno microcontroller board. This system is designed to assist users in detecting turbidity using a turbidity sensor. Based on testing, the success rate of this system is 93.27%.